(untitled) (Journal of the College of Basic Education, 2023)
Praise be to God, Lord of the worlds, and prayers and peace be upon the Seal of the Prophets and Messengers and upon his pure and pure family and his companions, the true fighters, and those who followed them in goodness until the Day of Judgment.And yet.Of God’s favor to people is that He brought them the Noble Qur’an that guides the straight path, and of His bounty is that qualified scholars prepared for it and interpreted it according to the fundamentalist approach in its interpretation and interpretation. This is an encouragement to rely on the Holy Qur’an in judging issues, especially social issues, and seeing what the commentators wrote in interpreting the Qur’anic verses, relying on transmission, reason and impact. The table is the title of my topic, this is on the one hand, and on the other hand, due to the West approaching the East and the mixing of Muslims with others in Islamic countries, considering them citizens and non-Islamic ones, after the migration of many Muslims to them recently, so I wanted to show what the Holy Qur’an permitted us in the matter of eating from their slaughtered animals. and marry their wives.